Vulnerable road users: Cross-cultural perspectives on performance and attitudes. (October 2020) - Yannis, George; Nikolaou, Dimitrios; Laiou, Alexandra; Stürmer, Yvonne Achermann; Buttler, Ilona; Jankowska-Karpa, Dagmara
Abstract: Pedestrians, cyclists and powered two-wheeler riders are considered vulnerable road users, as they are prone to a high risk of injury in the event of vehicular collision. This paper sought to elucidate the road safety performance and attitudes of vulnerable road users in 32 countries. In addition, comparisons between countries and demographic characteristics have been conducted, and recommendations that could enhance vulnerable road users' safety have been provided. For the study, data from the second edition of the ESRA survey ( E -Survey on Road Users' Attitudes – ESRA2) conducted in 2018 were utilized. The results indicate that crossing the road at places other than nearby pedestrian crossings, reading a text message or checking social media while walking on the streets, cycling and riding without wearing a helmet, and speeding on powered two-wheelers outside built-up areas but not on motorways/freeways were the most frequently reported self-declared behaviours in the 32 countries. Finally, some solutions on preventing road crashes and increasing vulnerable road users' safety such as infrastructure interventions, use of protective equipment, and training and educational campaigns are discussed. Highlights: Vulnerable road users are prone to a high risk of injury in any vehicular collision High rates of unsafe behaviours were reported by vulnerable road users Clear need for road safety measures that would enhance the safety of vulnerable road users ESRA survey is a valuable source of information and provides unique data on VRUs' performance